1958–2014: After 56 Years of Research, Cytochrome P450 Reactivity Is Finally Explained. Issue 19 (7th April 2014) - McQuarters, Ashley B.; Wolf, Matthew W.; Hunt, Andrew P.; Lehnert, Nicolai
<x xml:space="preserve">Abstract</x> Nature's wisdom in enzyme design: Compounds I and II in the catalytic cycle of the Cytochrome P450 enzymes have been trapped and characterized recently. This work has provided further insight into the electronic structure and reactivity of these crucial intermediates, and key questions regarding the mechanism of these enzymes have finally been answered.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>